Network support, technology use, depression, and ART adherence among HIV-positive MSM of color. Issue 9 (2nd September 2017) - Holloway, I.W.; Tan, D.; Dunlap, S.L.; Palmer, L.; Beougher, S.; Cederbaum, J.A.
ABSTRACT: Depression is associated with poor antiretroviral therapy (ART) adherence among people living with HIV/AIDS. This relationship may be moderated by an individual's social network characteristics. Our study sought to examine social network correlates of treatment adherence among HIV-positive men recruited from social service agencies throughout Los Angeles County ( N  = 150) to inform technology-driven social support interventions for this population. We administered egocentric social network and computer-assisted survey interviews focused on demographic characteristics, health history, depressive symptoms, and ART adherence, where adherence was assessed by the number of reasons participants missed taking their medication, if ever. Significant univariate correlates of adherence were included in a multivariable regression analysis, where the moderating effect of having a network member who reminds participants to take their HIV medication on the relationship between depression and adherence was tested. Over 60% of participants reported clinically significant depressive symptoms; this was significantly associated with lower adherence among those without someone in their social network to remind them about taking their HIV medication, even after adjusting for covariates in an ordinary least squares regression (adjusted mean difference b  = −1.61, SE = 0.42, p  = 0.0003). Having a network member who reminds participants to take their ART medication significantly ameliorated the negative association between depression and treatment adherence, especially for those reporting greater depressive symptoms ( p  = 0.0394). Additionally, participants demonstrated high rates of technology use to communicate with social network members. In order to achieve the aims of the National HIV/AIDS Strategy, innovative interventions addressing mental health to improve ART adherence are needed. Network strategies that leverage technology may be helpful for improving ART adherence among HIV-positive men with comorbid depressive symptoms.